2022
DOI: 10.3389/fmed.2022.892265
|View full text |Cite
|
Sign up to set email alerts
|

Dysnatremia in Gastrointestinal Disorders

Abstract: The primary solute of the milieu intérieur is sodium and accompanying anions. The solvent is water. The kidneys acutely regulate homeostasis in filtration, secretion, and resorption of electrolytes, non-electrolytes, and minerals while balancing water retention and clearance. The gastrointestinal absorptive and secretory functions enable food digestion and water absorption needed to sustain life. Gastrointestinal perturbations including vomiting and diarrhea can lead to significant volume and electrolyte losse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 57 publications
(82 reference statements)
0
0
0
Order By: Relevance
“…However, treatment with BGNCE increased the concentrations of the electrolytes in a dose-dependent manner. The results of concentrations of the electrolytes (potassium ion (K + ), sodium ion (Na + ) and chloride ion (Cl -) monitored in the experimental rats corroborated earlier reports by Do et al [15] that diarrhoeal condition leads to loss of body electrolytes. Treatment of castor oil-induced diarrhoeal rats with bambara groundnut condiment extract at all experimental doses improved the diarrhoeal condition of the rats.…”
Section: Electrolyte Concentrations (Na + K + Clions) In Serum Of D...supporting
confidence: 89%
“…However, treatment with BGNCE increased the concentrations of the electrolytes in a dose-dependent manner. The results of concentrations of the electrolytes (potassium ion (K + ), sodium ion (Na + ) and chloride ion (Cl -) monitored in the experimental rats corroborated earlier reports by Do et al [15] that diarrhoeal condition leads to loss of body electrolytes. Treatment of castor oil-induced diarrhoeal rats with bambara groundnut condiment extract at all experimental doses improved the diarrhoeal condition of the rats.…”
Section: Electrolyte Concentrations (Na + K + Clions) In Serum Of D...supporting
confidence: 89%
“…Chronic diarrhea in IBS-D may double or triple ordinary stool frequency[ 3 ]. In conjunction with stool quality of BSFS 6-7[ 7 ], IBS-D may increase daily bowel water losses to 500 mL[ 6 , 24 ] along with accompanying salt losses[ 8 , 25 ]. Although no measures of hydration status were made in this study, the complement of approximately 474 mL of fluid with approximately 30 mmol/L of key electrolytes consumed daily, alongside a significant reduction in BSFS from liquid to solid, makes plausible an improvement in whole body hydration status over the 2-weeks.…”
Section: Discussionmentioning
confidence: 99%
“…As for SOC of metabolism and nutrition disorders, hypokalaemia, electrolyte imbalance, and weight fluctuation are the main significant PT signals (Table 4). Previous reports have shown that severe diarrhea leads to loss of body fluids and electrolytes, which can lead to electrolyte imbalance, dehydration and renal insufficiency, and malnutrition (Do et al, 2022). In addition, nausea and vomiting can also lead to systemic complications metabolic imbalances and nutrient depletion (D'Arienzo et al, 2023).…”
Section: Socmentioning
confidence: 99%